Epigenetic insights into creep-feeding: methylation profiling of Longissimus thoracis muscle at weaning in crossbred cattle - Rodrigues, Lucas Farias; Ramírez-Zamudio, German Dario; Pereira, Guilherme Luis; Torrecilhas, Juliana Akamine; Trevisan, Lucas Augustinho; Machado Neto, Otávio Rodrigues; Chardulo, Luis Artur Loyola; Baldassini, Welder Angelo; Curi, Rogério Abdallah (Frontiers in Animal Science, 2024)
Introduction This study investigated the impact of creep-feeding supplementation on the genome methylation of the Longissimus thoracis (LT) muscle in crossbred beef cattle (Bos taurus × Bos indicus). Methods The experiment involved 48 uncastrated F1 Angus-Nellore males (half-siblings), which were divided into two groups: NCF – no creep-feeding (n = 24) and CF – creep-feeding (n = 24). After weaning at 210 days, all animals were feedlot finished for 180 days under identical conditions. LT muscle biopsies were collected at weaning for genomic DNA methylation analysis by reduced representation bisulfite sequencing (RRBS). Results and discussion The groups differed significantly (CF > NCF: p < 0.05) to weaning weight (243.57±5.70 vs. 228.92±5.07kg), backfat thickness (12.96±0.86 vs. 10.61±0.42mm), LT muscle marbling score (366.11±12.39 vs. 321.50±13.65), and LT intramuscular fat content (5.80±0.23 vs. 4.95±0.20%). The weights at the beginning of the experiment and at slaughter (390 days) did not differ significantly. Mean methylation levels were higher in CF with 0.18% more CpG, 0.04% CHG, and 0.03% CHH. We identified 974 regions with differential methylation (DMRs: > 25% and q < 0.05), which overlapped with 241 differentially methylated genes (DMGs). Among these genes, 108 were hypermethylated and 133 were hypomethylated in CF group. Notably, 39 of these DMGs were previously identified as differentially expressed genes (DEGs: log2 fold change [0.5]) in the same animal groups. Over-representation analysis highlighted epigenetic regulations related to muscle growth, PPAR signaling, adipogenesis, insulin response, and lipid metabolism. Key DMGs/DEGs included: ACAA1, SORBS1, SMAD3, TRIM63, PRKCA, DNMT3A, RUNX1, NRG3, and SLC2A8. These epigenetic changes improved the performance of supplemented animals up to weaning and enhanced meat quality traits, particularly higher intramuscular fat. The results provided insights into the intricate interplay between nutrition, epigenetics, gene expression and phenotypes in beef cattle production.